Effect of Including Cancer Mortality on the Cost-Effectiveness of Aspirin for Primary Prevention in Men - Pignone, Michael (Springer US, 2013)
BACKGROUND: Recent data suggest that aspirin may be effective for reducing cancer mortality. OBJECTIVE: To examine whether including a cancer mortality-reducing effect influences which men would benefit from aspirin for primary prevention. DESIGN: We modified our existing Markov model that examines the effects of aspirin among middle-aged men with no previous history of cardiovascular disease or diabetes. For our base case scenario of 45-year-old men, we examined costs and life-years for men taking aspirin for 10 years compared with men who were not taking aspirin over those 10 years; after 10 years, we equalized treatment and followed the cohort until death. We compared our results depending on whether or not we included a 22 % relative reduction in cancer mortality, based on a recent meta-analysis. We discounted costs and benefits at 3 % and employed a third party payer perspective. MAIN MEASURE: Cost per quality-adjusted life year (QALY) gained. KEY RESULTS: When no effect on cancer mortality was included, aspirin had a cost per QALY gained of $22,492 at 5 % 10-year coronary heart disease (CHD) risk; at 2.5 % risk or below, no treatment was favored. When we included a reduction in cancer mortality, aspirin became cost-effective for men at 2.5 % risk as well (cost per QALY, $43,342). Results were somewhat sensitive to utility of taking aspirin daily; risk of death after myocardial infarction; and effects of aspirin on stroke, myocardial infarction, and sudden death. However, aspirin remained cost-saving or cost-effective (< $50,000 per QALY) in probabilistic analyses (59 % with no cancer effect included; 96 % with cancer effect) for men at 5 % risk. CONCLUSIONS: Including an effect of aspirin on cancer mortality influences the threshold for prescribing aspirin for primary prevention in men. If such an effect is real, many middle-aged men at low cardiovascular risk would become candidates for regular aspirin use. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-013-2465-6) contains supplementary material, which is available to authorized users.